Enhancing the Tenth Grade Students' Vocabulary Achievement by Using Bingo Game at SMA NU Genteng - Triska Dayu Damayanti; Bambang Suharjito; Made Adi Andayani T (FKIP e-PROCEEDING, 2017)
Abstract: The purpose of this classroom action research was to improve the tenth grade students' vocabulary achievement and their active participation by using Bingo game at SMA NU Genteng. The method used in determining the research area and the research subjects was purposive method. The primary data were obtained from vocabulary test and observation checklist. Interview and documentation were used as  supporting data. The result of the vocabulary test and observation were analyzed quantitatively by using Ali's formula. The results of the students' active participation in meeting 1 was 63% and 81% in meeting 2. Meanwhile, the result of the students' vocabulary achievement improved from 26% (the test given by the teacher) to 75% (the test given by the researcher) in cycle 1. Therefore, it can be concluded that the use of Bingo game could imrpove the tenth grade students' vocabulary achievement and their active participation in the vocabulary teaching and learning process. Keywords: Bingo game, Students' Active Participation, Vocabulary Achievement